Young innovative companies and employment creation, evidence from the Pakistani textiles sector. (May 2019) - Wadho, Waqar; Goedhuys, Micheline; Chaudhry, Azam
Highlights: Innovation is an important driver of firm growth in the Pakistani textiles sector. Young innovative firms to catch up with incumbents by engaging in more radical innovation. Young innovative companies also outperform other firms in absolute employment creation. Abstract: Using unique innovation survey data collected among a homogenous sample of firms active in the textiles and apparel sector in Pakistan, this paper analyses the role of innovation for employment growth. In particular, it develops and tests the hypothesis that innovation is conducive to employment creation, and that this is especially the case for smaller and younger firms, supporting the hypothesis that young innovative companies grow faster by engaging in riskier and more radical innovation to catch up with incumbent firms. We find empirical evidence for these hypotheses, which is robust to different model specifications and estimation techniques and to different measures of innovation. Young innovative companies also perform well in absolute employment creation making them interesting targets from a policy perspective.